Large Reductions in Match Play Physical Performance Variables Across a Professional Football Season With Control for Situational and Contextual Variables - Springham, Matthew; Williams, Sean; Waldron, Mark; Burgess, Darren; Newton, Robert Usher (Frontiers in Sports and Active Living, 2020)
This investigation examined match play physical performance across a professional football season using a multi-camera computerized tracking system. A linear mixed-effects model, controlling for situational and contextual variables, identified decreases in team average total distance (TD): season quarter 1 (Q1) (11047 m) > season quarter 2 (Q2) (10473 m) (P=0.002; ES=Small), season quarter 3 (Q3) (10449 m) (P<0.001; ES=Moderate) and season quarter 4 (Q4) (10385 m) (P<0.001; ES=Moderate); work rate (WR): Q1 (115 m/min) > Q3 (108 m/min) (P<0.001; ES=Moderate), Q4 (107 m/min) (P<0.001; ES=Moderate); Q2 (109 m/min) > Q4 (107 m/min) (P=0.003; ES=Small); high-speed running distance (HSR): Q1 (1051 m) > Q2 (813 m) (P=0.006; ES=Small); number of high-speed runs (NHSR): Q1 (87) > Q2 (65) (P<0.001; ES=Small), Q3 (64) (P=0.002; ES=Small); sprint distance (SD): Q1 (202 m) > Q4 (130 m) (P<0.001; ES=Moderate), Q2 (179 m) > Q3 (165 m) (P=0.035; ES=Small), Q4 (130 m) (P<0.001; ES=Moderate) and number of sprints (NS): Q1 (20.4) > Q3 (10.2) (P<0.001; ES=Moderate), Q4 (8.3) (P<0.001; ES=Large); Q2 (14.9) > Q3 (10.2) (P<0.001; ES=Moderate), Q4 (8.3) (P<0.001; ES=Large). Within-position changes were observed for WR: Q1 (122 m/min) > Q4 (113 m/min) (P=0.002; ES=Large) in central midfielders and for NS: Q1 > Q3 in wide defenders (21.7 vs 10.8) (P=0.044; ES=Large) and central midfielders (18.1 vs 8.3) (P=0.002; ES=Large); Q1 > Q4 in central defenders (13.1 vs 5.3) (P=0.014; ES=Large), wide defenders (21.6 vs 7.1) (P<0.001; ES=Very Large), central midfielders (18.1 vs 8.5) (P=0.005; ES=Large) and wide midfielders (20.8 vs 12.2) (P=0.012; ES=Large); Q2 > Q3 in central midfielders (16.9 vs 8.3) (P=0.002; ES=Large) and Q2 > Q4 in wide defenders (16.3 vs 7.1) (P=0.005; ES=Very Large), central midfielders (16.9 vs 8.5) (P=0.004; ES=Large) and wide midfielders (20.8 vs 12.2) (P=0.007; ES=Large). Match-play physical performance reduced across the competitive season. The most notable reductions were observed in wide defenders, central midfielders and wide midfielders in sprint performance indices.